LINTASAN BELAJAR MATERI ARITMATIKA SOSIAL DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DI SMP NEGERI 1 BATANG ANGKOLA KABUPATEN TAPANULI SELATAN - Annisa, Putri; Rangkuti, Ahmad Nizar (Math Educa Journal, 2019)
The Purpose of the research is to find out validation and practically learning trajectory by realistic mathematics education approach of social arithmetic object in SMP Negeri 1 Batang Angkola. This research in research forming design research type validation study even the purposing developing local intruction theory (LIT) by compinion researcher and teacher to improving quality of learning. The action this research at SMP Negeri 1 Batang Angkola by experience subject of product in grade VII-A, leader 32 students. The instrument collecting data by using validation paper, questionnaire and using analysing validation technique and practicalitation. The result of research point out learning trajectory by realistic mathematics education approach said valid and practice. The validating source learning point out with score 76% by analyses 2 validator. The practicitation source learning find out with score 88% from questionnening respon of students, action all componens. Realistic Mathematics Education Approach to proccesing learning and extracted student in learning social arithmetic material. The source of learning resulting to this research forming activities action from reaching the purpose of learning, when purpose of learning are understanding social arithmetic concept.